Deskripsi Perbedaan Tingkat Kepuasan dengan Tingkat Kepentingan Peserta Pelatihan pada Pelayanan Balai Pelatihan Kesehatan di Batam - Supriyono, Supriyono (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2018)
This study aims to determine the picture of the relationship of differences in the level of satisfaction and the interests of trainees to the service in Batam of health training national. Population in this research is all training participant who use service. The sample in this research is saturated samples, where all the participants, with the number of respondents as many as 379 people. From the normality test results, obtained the result that all variables are no normal distribution, so the test used is Mann Whitney Test. The method of data collection is documentary search. The results of data processing are presented in the form of tables and graphs. From the satisfaction level obtained an average result of 5.38% stated not satisfied, with the worst service is on service to the complaint that is equal to 10% and best / highest in call center service While the average interest rate of 0.08% of respondents stated that it is not important, with service is not important in marketing services, administration and toilet that is each of 0.3%, and service complaints of 0.2%. The result of the research at 95% significance level obtained p value 0,00> 0,05 Thus it can be concluded that there is no difference of level of satisfaction and level of importance to service in Batam of health training national at 2016.